In Centrifugal-Vibration Concentrators Gravitational Enrichment - Abdusamiyeva Lobarxon No‘monjon qizi; Ashirmatova Iroda Mamasaid qizi; Jo‘raqulova Sabrina Baxtiyor qizi (Research Parks Publishing LLC, 2023)
Centrifugal-vibration concentrators represent a vital tool in the field of mineral processing and ore beneficiation. This article delves into the fundamental concept of